2014
DOI: 10.1159/000367587
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Natural History of Intracranial Arterial Stenosis: An MRA Follow-Up Study

Abstract: Background: Intracranial arterial stenosis (ICAS) is a major cause of ischemic stroke in Asians. Despite the clinical importance of ICAS, the literature on the natural history of ICAS has been less enlightening. The aims of our study were to evaluate a long-term natural course of symptomatic and asymptomatic ICAS. Methods: 102 subjects (37 symptomatic and 65 asymptomatic) underwent follow-up MR angiography (MRA) with a median time interval between initial and follow-up MRA of 5.7 years (range 3.6-8.5 years). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…This has been reported in cases of intensive medical management alone, which is maintained in all patients undergoing EDAS in this study. 11,33 While this observation supports the notion that the decrease in the venous probability derived from probabilistic ICA acts as a surrogate for revascularization, it raises a second interesting question: one might inquire whether the observed relationship between increased venous probability and post-operative revascularization might qualify as a marker for patient selection and/or a valuable tool for surgical planning and monitoring. While this is beyond the scope of this initial study, it is well worth following up in a systematic study of a larger size.…”
Section: Discussionmentioning
confidence: 58%
“…This has been reported in cases of intensive medical management alone, which is maintained in all patients undergoing EDAS in this study. 11,33 While this observation supports the notion that the decrease in the venous probability derived from probabilistic ICA acts as a surrogate for revascularization, it raises a second interesting question: one might inquire whether the observed relationship between increased venous probability and post-operative revascularization might qualify as a marker for patient selection and/or a valuable tool for surgical planning and monitoring. While this is beyond the scope of this initial study, it is well worth following up in a systematic study of a larger size.…”
Section: Discussionmentioning
confidence: 58%
“…Ryu et al. () studied 102 subjects with ICAS and found that symptomatic ICAS subjects had greater risk of stenosis progression than asymptomatic ones. In carotid arteries, a number of studies have shown that presence of intraplaque hemorrhage (Sun et al., ; Takaya et al., ), maximum wall thickness (Xu et al., ), maximum lipid‐rich necrotic core percentage (Xu et al., ), and negative remodeling (Bianda et al., ) determined by MR vessel wall imaging are effective predictors for carotid plaque progression.…”
Section: Discussionmentioning
confidence: 99%
“…For subjects who were diagnosed with ICAD ( n > 200), the clinical follow‐up will be conducted at 3, 6, 12, and 24 months and the MR imaging follow‐up will be performed at 12 and 24 months, respectively. Previous studies reported that the progression rate of ICAS was 3.86% per year (Ryu et al., ) and the intra‐reader and inter‐scan variation in measuring maximum wall thickness of intracranial plaques was 6.67% (Zhang et al., ). Therefore, it might be reasonable to detect the 2 years’ progression of intracranial atherosclerosis disease (7.72%) which is greater than the variation of quantitative measurement by MRI.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Opinions regarding the management of intracranial stenoses are varied [34]. There should be further clarification of the stenosis (Category II) if the stenosis is > 50 % or extensive WMH is ascertained (Fazekas Grade II/III) [35], since stenosis progression or the risk of a cerebrovascular event is raised [33].…”
Section: Intracranial Stenosismentioning
confidence: 99%